Use of a Webpage in Designing Employee Data Collection at the Aceh Language Center Office - Safrinal Safrinal; Inyak Sukendi; Supriyanto Supriyanto; Afrizal Afrizal (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2021)
The employee information system is one of the data processing activities at the Aceh Language Hall Office, to get information about employees to be more focused and easy to obtain. In this study, researchers only discussed employee problems and data management mechanisms at the Aceh Language Center Office and designed an employee data collection information system using PHP and MySQL. The research objective was to understand the problems of employees and data management at the Aceh Language Center Office and to create a supporting application about employee information systems using PHP and MySQL. The collection of data needed in writing this report was obtained by two methods, namely literature studies related to literature, library books, and other scientific works, field studies by conducting interviews, and direct observation of objects related to this research. The employee information system is carried out by one of the administrative staff and assisted by 2 (two) employee administration staff to record and input employee data. From the results of the study, it can be concluded that the employee information system at the Aceh Language Hall Office has followed the procedure and uses a computer with the PHP and MySQL language programs as the database.